Training and Teaching English in Corporate set up: the Dichotomy - Girish Prasad Rath (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Training is any planned activity designed and performed to help an individual or a group to perform a job or a task effectively. The need for training arises when there is a gap between what the employer requires and what the employees are able to deliver. The difference between the entry level and the target level of a learner or a group of learners is the training gap. A training gap highlights what the focus of training should be. It refers to what needs to be achieved on a particular course. It is arrived at by establishing the entry level and needs analysis. The training gap relates only to the differences between current level and the target level as defined by the job needs. It may not be uniform across the different language skills nor will the gap be uniform within a skills area. It is seen in various organizations that training helps in career progression and should be planned to meet corporate goals and objectives. It must be treated as a development process rather than as a series of isolated events The competitiveness among organizations leads them to conduct training programmes for their employees so that they can upgrade their skills and became self-reliant. To understand the concept of training better, we need to look at the characteristics of training and education